Answer:

A reflection of the line segment across the line y = –x.

Step-by-step explanation:

Given : A line segment has endpoints at (–1, 4) and (4, 1).

To find : Which reflection will produce an image with endpoints at (–4, 1) and (–1, –4).

Solution : We have given that endpoints at (–1, 4) and (4, 1).

After reflection endpoints become  (–4, 1) and (–1, –4).

Reflection:   (–1, 4)  →→ (–4, 1)

                    (4, 1)→→→ (–1, –4).

We can see x coordinate become -y coordinate and y coordinate become -x coordinate.

(x ,y) →→ (–y, -x)

This is the a reflection of the line segment across the line y = –x rule of reflection .

Therefore, a reflection of the line segment across the line y = –x.